Bubble Detection and the Impact of Monetary Policy, Market Sentiment and Market Liquidity on Property Stock Price Index in Indonesia - Dasman, Sunita (Archives of Business Research, 2021)
The purpose of this study is to detect the existence of a bubble stock and analyze the impact of monetary policy, market sentiment and liquidity on the property stock index in the Indonesian capital market. The data used in this study is secondary data originating from various sources for the period 2016 – 2020 using multiple linear regressions. The bubble stock detection is done by using the ratio between the property stock price index and the consumer nutrient index. The results showed that there was an indication of a moderate bubble stock in the property stock index during the research period 2016 – 2020. The factors that impacted the property stock price index were interest rates, the rupiah exchange rate against the US dollar, market sentiment and market liquidity. The increase in interest rates, the rupiah exchange rate, and market sentiment and liquidity has an impact on the increase in the property stock price index on the Indonesian stock exchange for the 2016 – 2020 periods. Keywords: Bubble Stock, Exchange Rate, Interest Rate, Inflation, Market Sentiment, Market Liquidity